Assistance in Coffee-Based Food Creation with Techno Kopi Bringka : IT-Based Coffee Processing MSMEs in Balegede Village, Naringgul Subdistrict, Cianjur Regency - Merdiani, Wentri; Mulyadi, Mulyadi; Hartati, Tuti (Edumedia Solution, 2025)
This assistance program aims to enhance the economic capacity of coffee processing SMEs, particularly the Techno Kopi Bringka MSME, in Balegede Village, Naringgul Subdistrict, Cianjur Regency. The program focuses on product diversification, the application of modern technology, and managerial training. Balegede Village boasts 500 hectares of coffee plantations, offering significant potential for the development of a coffee-based creative economy. The program incorporates the use of modern production technologies, including grinding, drying, and coffee roasting machines, alongside information technology systems for management and e-commerce. A participatory approach is adopted, actively involving the community in all stages, from planning to evaluation. The program outcomes demonstrate a twofold increase in the production capacity of Techno Kopi Bringka MSME, resulting in the creation of various innovative coffee-based products, such as snacks, processed beverages, and other derivatives. Furthermore, SME market access has been expanded through digital marketing and e-commerce platforms. The program also successfully improved managerial skills, operational efficiency, and SME income, with a projected sales increase of up to 50%. Through the implementation of IT-based management systems and product diversification, Techno Kopi Bringka MSME has successfully reached broader markets, both domestic and international. This program underscores how the integration of technology and innovation can drive sustainable local economic growth, enhance SME competitiveness, and strengthen the coffee-based creative economic ecosystem in Balegede Village, delivering both economic and social benefits to the local community.